Pengembangan E-Modul Berbasis Mastery Learning Untuk Mata Pelajaran KKPI Kelas XI - Luh Putu Eka Diantari; Luh Putu Eka Damayanthi; Nyoman Sugihartini Sugihartini; I Made Agus Wirawan (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2018)
Abstract— The aims of this research are: (1) To develop e-modul mastery learning teaching model of KKPI toward XI grade students at SMKN 1 Sawan, (2) To know both students and teachers response toward the development to realitation e-modul mastery learning teaching model of KKPI toward XI grade students at SMKN 1 Sawan. The design of this research was R&D (research and development) research design accompanied with the development model of PLOMP. The subject of this research was all XI grade students at SMKN 1 Sawan academic year 2017/2018. In order to know both teachers and students response toward the e-modul KKPI, the researcher used questionnaire. This research shows that: (1) the development of realitation e-modul mastery learning teaching model of KKPI toward XI grade students at SMKN 1 Sawan have been successfully realitation looking at several tests have been done by the researcher. (2) Based on the analysis of the data of teacher's response score of 45, if this converts into table of response categorization, it belongs to very positive category. Furthermore, based on the analysis of the data of students' response, on the other hand, shows the mean score of 65,70. If it is converted into table of response categorization, it belongs to  positive category.